Nilai Anak Pada Usia Subur yang Menunda Kehamilan Pertama: (Studi Kasus Pada Lima Pasangan Ussia Subur di Kota Pekanbaru) - Fatimah Azzahra; Susanti, Rina (Arden Jaya Publisher, 2024)
Couples of childbearing age who postpone the first pregnancy in Pekanbaru City are a decision, as in Max Weber's social action, namely the actor is influenced by an action. The purpose of this research is to find out the background of couples of childbearing age delaying the first pregnancy and the views of couples of childbearing age on the value of children. The technique in stopping informants using Purposive Sampling technique. The subjects in this study amounted to five couples of childbearing age who delayed pregnancy using contraceptives or birth control. The results showed that based on the field findings of the social action theory background by Max Weber, there is instrumental rationality which is influenced by economics, work rules, and careers. Value rationality is influenced by readiness factors. The irrational background is affective or affective actions influenced by affection factors and traditional actions influenced by family encouragement so that the decision to delay the first pregnancy using family planning. The value of children seen from couples of childbearing age based on field findings obtained from interviews shows that there are four values of children, namely spiritual, psychological, social, and economic. Spiritual values found that couples of childbearing age who postpone the first pregnancy view the value of children, namely children are a gift for those who are ready and entrusted by God. The psychological value is that couples of childbearing age who postpone their first pregnancy view the value of children as entertainment, encouragement, and readiness as parents. Then from the social value that couples of childbearing age who postpone the first pregnancy see the value of children as the successor of offspring, and the binding of a large family. The economic value is that couples of childbearing age who postpone their first pregnancy see the value of children as a burden, investment, and security in old age.